Research into the Effect of Supercapacitor Terminal Voltage on Regenerative Suspension Energy-Regeneration and Dynamic Performance - Ruochen Wang; Yanshu Ding; Qing Ye; Renkai Ding; Jingang Qian (Shock and Vibration)
To study the effect of supercapacitor initial terminal voltage on the regenerative and semiactive suspension energy-regeneration and dynamic performance, firstly, the relationship between supercapacitor terminal voltage and linear motor electromagnetic damping force and that between supercapacitor terminal voltage and recycled energy by the supercapacitor in one single switching period were both analyzed. The result shows that the linear motor electromagnetic damping force is irrelevant to the supercapacitor terminal voltage, and the recycled energy by the supercapacitor reaches the maximum when initial terminal voltage of the supercapacitor equals output terminal voltage of the linear motor. Then, performances of system dynamics and energy-regeneration were studied as the supercapacitor initial terminal voltage varied in situations of B level and C level road. The result showed that recycled energy by the supercapacitor increased at first and then decreased while the dynamic performance had no obvious change. On the basis of previous study, a mode-switching control strategy of supercapacitor for the regenerative and semiactive suspension system was proposed, and the mode-switching rule was built. According to simulation and experiment results, the system energy-regeneration efficiency can be increased by utilizing the control strategy without influencing suspension dynamic performance, which is highly valuable to practical engineering.